Negotiating movement: everyday immigration policing in Johannesburg - Tshabalala, Xolani (My University, 2010)
Abstract Volumes of cross-border migration into South Africa have substantially increased in recent years, and so have state efforts to regulate them. This has meant that as migrants go about their day-to-day activities, they have had to endure closer scrutiny from state police officials who enforce immigration laws deep within South Africa, away from the country’s borders. Students of political economy may question how the resulting interaction between migrants and state officials at the street level impacts on state construction in the developing world. This research is a result of about four months of (non-)participant observation conducted with police officials in inner-city Johannesburg. Additional data was obtained from official documents as well as semi-structured and informal interviews with both police officials and migrants. The findings from this research suggest that in the case of South Africa, it may be premature to posit a state that has been ‘cannibalized’ by society, as some may suggest. State officials consistently and sometimes overzealously profile, interrogate and arrest suspected undocumented migrants. Migrants are themselves aware and wary of imminent arrest and possible deportation should they move around without their permits. For state officials, this has sometimes even entailed the use of seemingly excessive means to enforce immigration law and to protect the state’s monopoly over regulating movement. Nonetheless, such efforts by the state exist within other informal, non-state and culturally embedded logics of interaction so commonly practiced by many societies the world over. On the one hand, these represent centuries old logics of negotiation, gift-giving and 7 networking. On the other, such logics are being reinvented to include bribery, extortion, predatory authority and other forms of exchange between migrants and state officials. The successive and sometimes simultaneous appeal to these different registers on both sides of the ‘point of enforcement’ in the course of immigration policing constantly shifts, redraws and blurs the boundaries between the formal and the informal, the legitimate and the illegitimate, and between the state and society. Both the political science and anthropological readers must face up to these everyday realities of the South African state.